1981
DOI: 10.1038/290020a0
|View full text |Cite
|
Sign up to set email alerts
|

The structure of eight distinct cloned human leukocyte interferon cDNAs

Abstract: Eight classes of human leukocyte interferon (LeIFN) cDNA clones have been identified in a cDNA library prepared from a myeloblastoid cell line. The nucleotide sequences demonstrate that the multiple human LeIFN genes code for a family of homologous, yet distinct proteins. One of the cDNA clones may have been derived from the transcription of a LeIFN pseudogene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
186
0
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 496 publications
(193 citation statements)
references
References 41 publications
6
186
0
1
Order By: Relevance
“…(c) Several cytokine genes and proto-oncogenes that contain the AUUUA consensus sequence in their 3'-UTRs. Abbreviations: Hu=human; mda-7=melanoma di erentiation associated gene-7 (Jiang et al, 1995a); a-IFN=alpha interferon (Goeddel et al, 1981); GM-CSF=granulocyte-monocyte colony stimulating factor (Wong et al, 1985); TNF=tumor necrosis factor (Nedwin et al, 1985); cFos=fos proto-oncogene (van Straaten et al, 1983) Several studies on intrinsically unstable mRNAs demonstrate that drugs, which inhibit protein synthesis, increase their stability (Raj and Pitha, 1981;Elder et al, 1984;Linial et al, 1985). The e ect of protein synthesis inhibitors was tested using cycloheximide, a compound that inhibits peptide bond formation.…”
mentioning
confidence: 99%
“…(c) Several cytokine genes and proto-oncogenes that contain the AUUUA consensus sequence in their 3'-UTRs. Abbreviations: Hu=human; mda-7=melanoma di erentiation associated gene-7 (Jiang et al, 1995a); a-IFN=alpha interferon (Goeddel et al, 1981); GM-CSF=granulocyte-monocyte colony stimulating factor (Wong et al, 1985); TNF=tumor necrosis factor (Nedwin et al, 1985); cFos=fos proto-oncogene (van Straaten et al, 1983) Several studies on intrinsically unstable mRNAs demonstrate that drugs, which inhibit protein synthesis, increase their stability (Raj and Pitha, 1981;Elder et al, 1984;Linial et al, 1985). The e ect of protein synthesis inhibitors was tested using cycloheximide, a compound that inhibits peptide bond formation.…”
mentioning
confidence: 99%
“…We report here the partial amino acid sequence ofmajor species ofhuman leukocyte interferon. These proteins, which represent a significant fraction of the active interferon produced by these cells, lack the 10 COOH-terminal amino acids suggested previously (11)(12)(13)(14) from the DNA sequences. Each of the three species is active although lacking the 10 COOH-terminal amino acids.…”
mentioning
confidence: 68%
“…Both of these residues were determined from leukocyte interferon a1. Because position 1 is Cys in all our recombinant cDNA and genomic clones (14,16,17) and those of Nagata et al (15), we assume the Ser found by us (7) and Zoon et al (6) may represent an artifact of the microsequencing procedures or modifications of the protein introduced during production and isolation. Although no NH2-terminal cysteine has been found in any of the natural leukocyte interferons (6,7,9), we have found Cys at the NH2 terminus of IFLrA produced inEscherichia coli (31,32).…”
mentioning
confidence: 76%
See 2 more Smart Citations